WORK AND HEALTH: ACCESS TO HEALTH CARE FORMAL WORKERS IN ARGENTINA - Fidalgo, Maitena (2013)
This article seeks to reflect on the ways of access to health services of formal workers in Argentina. The history of the social protection system has been at the link “formal work-health protection” as reference axis in the allocation and recognition of rights. The interest is to do an analysis about the transformation of the social protection system associated with the work being redefined from the neoliberal reform process of the 90’s.